The Impact of Work-Life Balance and Professional Competence on the Psychological Well-Being of Elementary School Teachers - Wibawa, Bebet Adi; Kusumaningsih, Widya; Soedjono, Soedjono (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to examine the influence of work–life balance and professional competence on the psychological well-being of elementary school teachers in Singorojo Subdistrict, Kendal Regency. The research employed a quantitative explanatory design using a survey method. The population consisted of 246 permanent elementary school teachers working in 35 public elementary schools. Using the Slovin formula with a 5% margin of error, a sample of 152 teachers was selected through proportionate stratified random sampling to ensure adequate representation from each school. Data were collected through validated Likert-scale questionnaires and analyzed using simple and multiple linear regression. The results show that: (1) work–life balance has a significant effect on psychological well-being (t = 13.593, p < 0.05) with a contribution of 55.2% (R² = 0.552); (2) professional competence significantly influences psychological well-being (t = 8.708, p < 0.05) with a contribution of 33.6% (R² = 0.336); and (3) both variables simultaneously have a significant effect on psychological well-being (F = 107.324, p < 0.05) with a combined contribution of 59% (R² = 0.590). These findings indicate that teachers’ psychological well-being is shaped by their ability to maintain work–life balance and by their level of professional competence. Strengthening these two aspects is essential for supporting teacher welfare and improving the quality of education, particularly in rural elementary school contexts.